Investigation of the plaque morphology effect on changes of pulsatile blood flow in a stenosed curved artery induced by an external magnetic field. (August 2021) - Teimouri, Kowsar; Tavakoli, Mohammad Reza; Ghafari, Ashkan; Kim, Kyung Chun
Abstract: In a new therapeutic technique, called magnetic drug targeting (MDT), magnetic particles carrying therapeutic agents are directed to the target tissue by applying an external magnetic field. Meanwhile, this magnetic field also affects the blood as a biomagnetic fluid. Therefore, it is necessary to select a magnetic field with an acceptable range of influence on the blood flow. This study investigates the effect of an external magnetic field on the pulsatile blood flow in a stenosed curved artery to identify a safe magnetic field. The effects of a number of parameters, including the magnetic susceptibility of blood in oxygenated and deoxygenated states and the magnetic field strength, were studied. Moreover, the effect of the plaque morphology, including the occlusion percentage and the chord length of the stenosis, on changes in blood flow induced by the magnetic field was investigated. The results show that applying a magnetic field increases the wall shear stress (WSS) and the pressure of the deoxygenated blood. Comparing the wall shear stresses of the deoxygenated and oxygenated blood shows that the effect of magnetic field on the deoxygenated blood is more significant than its effect on the oxygenated blood due to its higher magnetic susceptibility. The study of the stenosis geometry shows that the influence of magnetic field on the blood flow is increased by decreasing the occlusion percentage of the artery. Furthermore, among the evaluated lengths, the 50° chord length results in the highest variation under the influence of the magnetic field. Finally, the magnetic field of Mn = 2.5 can be utilized as a safe field for MDT purposes in such a stenosed curved artery. Highlights: The effect of magnetic field on pulsatile blood flow in a stenosed curved artery was investigated. Both states of oxygenated and deoxygenated blood were considered. The occlusion percentage and the chord length of stenosis, as important parameters, were studied. A safe magnetic field with no significant effect on blood hemodynamics was presented by analyzing the WSS and the pressure.